The prevalence of musculoskeletal injuries in junior elite squash players - Horobeanu, C.; Johnson, A.; Pullinger, S. A. (Asian Journal of Sports Medicine, 2019)
Background:The dynamics and competitiveness of squash place a high demand on the musculoskeletal system of players, thus increasing the injury risk of youth squash players.